STUDY OF DIRECT AND INDIRECT CONVERSION TYPE NUCLEAR BATTERY DESIGN USING PM-147 AND SR-90 BETA RADIATION SOURCES BASED ON P-N JUCTION SEMICONDUTOR - Rahastama, Swastya
The decay of radioactive element due to an unstable nucleus resulted in an emission of high energy subatomic particle, one of them is the beta radiation. This type of radiation can be utilized as the source of energy in nuclear battery using semiconductor as the radiation-electricity converter. The beta emitter such as H-3, Ni-63, Pm-147, and Sr-90 are among the most promising candidates to be used in ionization based nuclear battery due to their decay scheme, decay energy, and long half-life. Pm-147 and Sr-90 are heavily produced in nuclear reactor by the fission process. Both of these isotopes have a higher decay energy compared to the other two candidates, thus theoretically they could provide a tremendous power output of the battery. However, the major issue for the betavoltaic battery is the low conversion efficiency from radiation to electricity. The uneffective process of beta particle interaction with semiconductor to generate elektron-lubang pairs compared to photon, might be the dominant problem which is responsible for the low conversion efficiency issue, although the betavoltaic opearation is nearly similar to the photovoltaic. One of the way to resolve this particular issue is the introduction of passivation layer between the metal contact and semiconductor. The technique has been used in the photovoltaic to reduce the high recombination losses at the surface. Moreover, the phosphor material can be introduced to improve the total conversion efficiency by having a hybrid source of beta and photon, which is known as radioluminescent light source (RLS). Zinc sulfide (ZnS) is one of the phosphor material which is able to emit visible light when being exposed to high energy radiation. By using Pm-147 or Sr-90 along with ZnS, the hybrid RLS source can be made by optimizing the thickness of ZnS. Besides, it can be easily doped with other metals such as copper, aluminum, or manganese to alter its physical properties. The simulation of nuclear battery is necessary since it could allow us to evaluate the design of the battery before the fabrication process take place. The nuclear battery simulation method still being developed, which one of the leading and accurate model for p-n junction betavoltaic is based on the minority carrier diffusion equation with exponential decay generation model. For 1-D case, the exact solution can still be obtained though it requires time and effort to derive such equation with specific boundary conditions. However, if we deal with a more complex generation model or a higher dimentional case, the analytical expression becomes more complicated and rather difficult to be solved. In this study, we tried to develop the simulation program using numerical method to evaluate the performance of Pm-147 and Sr-90 nuclear battery. The model for calculation is based on the minority carrier diffusion equation which is taken from the photovoltaic theory with a modified generation rate model. Since it is based on second order differential equation, the 2-D finite difference scheme can be used as the numerical method. The result from the numerical calculation is compared to the 1-D exact calculation to be evaluated. The generation model requires beta energy deposition data which is calculated with the aid from Monte Carlo N-Particle X (MCNPX) code. The analytical and numerical approach were evaluated to the previous study by using Pm-147 and silicon semiconductor with the variation in radioactivity. At first, the betavoltaic system with ideal surface state were studied. The condition of the surface contact is one of the determining factors of the recombination loss, which reduce the betavoltaic electrical performance. Moreover, the indirect conversion nuclear battery code was built by using the ZnS:Cu phospor material which has been studied previously. However, the 2-D numerical simulation produced a closer result to the experimental data compared to the 1-D analytical calculation. The results of betavoltaic simulation shows that Sr-90 source could give a higher maximum power output due to its tremendous decay energy, but produced a lower conversion efficiency compared to Pm-147. The verification to the experimental data shows that a high level of surface recombination existed on both surface, which the recombination of lubang in the front surface dominates due to the lack of passivation layer as shown in the detailed description of the device by Lawrence etc. The amplification of source radioactivity in betavoltaic battery, however, degraded the total conversion efficiency. On the other hand, the Pm-147/ZnS:Cu RLS giving a different behavior which the amplification of radioactivity could still increased the conversion efficiency, although the saturation pattern is observed. The beta-light conversion efficiency from our simulation resulted a close pattern to the previous experimental and simulaton work from Hong etc. However, we obtained the optimum mass thickness of ZnS:Cu about 18 mg/cm2, which is only a several magnitude different from previous study. In general, from our simulation work, the indirect conversion scheme shows a better promise to the total conversion efficiency than the conventional betavoltaic battery. This also confirms that the interaction between photon and semiconductor is much more effective to generate elektron-lubang pairs compared to the beta particle. Hopefully, there is a further progress in the development of our code which can also be validated through own experiments.